THE DEVELOPMENT OF DECISION SUPPORT SYSTEM USING TOPSIS (TECHNIQUE FOR ORDER PREFERENCE BY SIMILARTY TO IDEAL SOLUTION) METHOD FOR TENDER PROCUREMENT PROJECT (A Case Study in Health Polytechnic Denpasar) - Ida Bagus Gede Palguna (Universitas Pendidikan Ganesha, 2012)
Nowadays, the auction of goods / services are often done by arranging directly a meeting between goods / services providers and consumers. Arranging a meeting between goods / services providers and consumers directly have some weaknesses; one of them is the probability of conspiracy. It will take a long time if there are a lot of participants of tenders and it sometimes makes them tired of waiting. Besides that, the difficulty which is usually faced by the consumers is they often face a situation where they have to choose one of choices provided. In taking a decision for the best choice, the data and information which have been measured by certain value are needed. The capability of taking a right decision is really needed. The decision support system as one of approaches to solve the problems above has to be very effective and efficient which be able to ease the committee to decide the winner of the tender. The process of taking the decision by using TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method uses several stages of System Development Life Cycle (SDLC) procedure. The stages of SDLC used consist of (1) the stage of collecting data by using library research method, observation and interview, (2) the stage of software requirement analysis by using TOPSIS method, (3) the stage of software designing, (4) the stage of developing or software implementation, and the last stage (5) testing stage. This software is implemented by using web-based application with the PHP programming language and MySQL as its database. The result of the implementation of the method and application is the decision support system which can be operated easily and helpful in taking the decision. It also makes the process of tender selection in Health Polytechnic Denpasar which usually takes a long time and boring becomes more efficient and effective.